Epoxy as an Alternative Resin in Particleboard Production with Pine Wood Residues: Physical, Mechanical, and Microscopical Analyses of Panels at Three Resin Proportions - Santos Junior, Antonio José [UNESP]; Herradon, Marjorie Perosso [UNESP]; de Souza, Matheus Viana [UNESP]; da Silva, Sergio Augusto Mello [UNESP]; De Araujo, Victor Almeida [UNESP]; de Almeida, Diego Henrique; dos Santos, Herisson Ferreira; Christoforo, André Luis [UNESP] (MDPI, 2025)
Given the construction challenges and the impacts of industrial waste generation and the implications of using chemical adhesives, this study aims to evaluate epoxy as an alternative resin, whose application in the production of wood particleboards is still underexplored. In this regard, its results were compared with those of widely used adhesives, such as urea-formaldehyde (UF). Pine wood particles were used, and epoxy resin was applied as a binder in 5%, 10%, and 15% proportions. Panels were manufactured under pressing parameters of 5 N/mm2 for 10 min at 110 °C. Physical and mechanical properties of panels were evaluated using Brazilian, European, and American standards. The results showed that epoxy resin is potentially convenient for the particleboard industry, as the 15% trait panels met the P4 class criteria in the Brazilian and European standards and D-2 for the American code, and the 10% trait panels achieved the M-3i class for the American document. Although 5% adhesive was insufficient to envelop wood particles, these traits with greater percentages reached high enveloping ratings in the scanning electron microscopy (SEM) test, making epoxy resin viable for the panel industry as a potential alternative to formaldehyde-based adhesives.
Keywords: epoxy resin; particleboard; pine; wood panel